Carotid Artery Perivascular Adipose Tissue Density Relates to Recanalization and Clinical Outcome After Mechanical Thrombectomy - Jin, Jiaolei; Huang, Rui; Chen, Qiuyue; Ke, Boxi; Tao, Taotao; Zhao, Rong; He, Xinwei (Frontiers in Aging Neuroscience, 2021)
Background: Perivascular adipose tissue (PVAT) imaging can be used in clinical practice as a surrogate marker of vascular disease. We aimed to analyze the association between the density of carotid artery PVAT and clinical features and outcomes in stroke patients treated with mechanical thrombectomy. Methods: A total of 183 consecutive patients treated with mechanical thrombectomy due to anterior circulation large vessel occlusion were retrospectively included from January 2016 to May 2021. The density of carotid artery PVAT was evaluated by preoperative computed tomography angiography. Successful arterial recanalization was defined as a modified Thrombolysis in Cerebral Infarction score of 2b-3 on the final angiographic examination. Poor functional outcome was defined as a modified Rankin Scale (mRS) score > 2 at 3 months after stroke. We assessed the independent effect of carotid artery PVAT density on revascularization, functional outcome, and mortality using logistic regression models adjusted for relevant confounders. Results: Patients with large artery atherosclerotic stroke have higher carotid artery PVAT density than patients with other stroke etiologies (–65.82 ± 12.96 vs. –75.77 ± 13.44, P < 0.001). Higher carotid artery PVAT density was associated with unsuccessful recanalization [adjusted odds ratio (AOR) (95% CI), 2.968 (1.292, 6.819), P = 0.010], and poor outcome [AOR (95% CI), 2.704 (1.610, 4.541), P < 0.001] and mortality [AOR (95% CI), 1.894 (1.040, 3.449), P = 0.037] at 3 months in stroke patients treated with thrombectomy. Conclusion: Higher carotid artery PVAT density before mechanical thrombectomy is an indicator of worse postprocedural arterial revascularization and a worse functional outcome in acute stroke patients.